Penerapan Kesehatan Dan Keselamatna Kerja (K3) Wisata Arung Jeram Di Pinus Camp, Desa Sumberbulu, Kabupaten Banyuwangi Sebagai Daya Tarik Wisata - Miftahol Arifin; Made Sukana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Badeng river is one of rafting location in Sumberbulu Village, Songgon District, Banyuwangi Regency. It has river grade approximately about 2 – 3 where the difficulty for rafting for beginner is still doable. Therefore, rafting in Pinus Camp can be made for tourist attraction. However, it is inevitable that having an activity in a wild nature can cause risk threatening the tourists’ safety. But, if it is done by maximum preparation as possible, it can minimize the unwanted risk. This research aim is to know the rafting activity in Pinus Camp and the implementation of Occupational Health and Safety (K3) on rafting in Pinus Camp as attraction in Badeng river. To collect the data of this research are observation, interview, and documentation. In analyzing used of this is a qualitative descrptive the tourism development and the influence of tourism development toward the physical environment. To have a ruslt of the research related to rafting in Pinus Camp are 3 activities, those are; Rafting, Tubing, and Riverboarding. For rafting and tubing, there are 4 trip packages, those are; long trip package, wonderful trip package, fun trip package and education trip. And for the riverboarding, it doesn’t have any packages yet because the activity is only used for the Pinus Camp guides. And for the results of Occupational Health and Safety (K3) implementation on rafting activity in Pinus Camp as attraction in Badeng river consists of 8 criteria, those are: 1. Occupational Health and Safety (K3) on white water rafting for tour guides, 2. K3 on coordinating and operating rafting tours, 3. K3 on leading the boat crew when doing a rafting, 4. K3 on rafting equipments preparation, 5. K3 on giving direction and debriefing of rafting techniques to boat crews, 6. K3 on anticipating emergency situations and conditions, 7. K3 on developing knowledge about the characteristics of rivers and rapids, 8. K3 of communicated by radio communication (HT) and signals. Keywords: Occupational Health and Safety (K3), Rafting Activities, and Tourist Attraction